A q-VARIANT OF STEFFENSEN'S METHOD OF FOURTH-ORDER CONVERGENCE - Ashour, Ola Abdelnaby (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Starting from q-Taylor formula, we suggest a new q-variant of Stef-fensen's method of fourth-order convergence for solving non-linear equations.